User mode Linux. - Dike, Jeff, ....- (Upper Saddle River : Prentice Hall, 2006)
With User Mode Linux you can create virtual Linux machines within a Linux computer and use them to safely test and debug applications, network services, and even kernels. You can try out new distributions, experiment with buggy software, and even test security. Now, for the first time, the creator and maintainer of User Mode Linux shows how to put it to work hands-on. Jeff Dike covers everything from getting started through running enterprise-class User Mode Linux servers. You'll find authoritative advice on bootup, compilation, administration, specialized configurations, and much more. Coverage includes: what User Mode Linux is, how it works, and its uses in Linux networks; key applications, including server consolidation, development, and disaster recovery; booting and exploration: logins, consoles, swap space, partitioned disks, and more; Copy-On-Write (COW): UML's efficient approach to storing filesystem changes; in-depth discussion of User Mode Linux networking and security; centrally managing User Mode Linux instances, and controlling their hardware resources; implementing clusters and other specialized configurations; setting up User Mode Linux servers, step-by-step: small-scale and large-scale examples; and the future of virtualization and User Mode Linux. Whether you're a netadmin, sysadmin, teacher, student, or programmer, "User Mode Linux[registered]" - the technology and this book - is indispensable.
Keywords: Linux (operating system).